The Moderating Effect of Market Turbulence on Innovation, Strategic Marketing, and Its Influence on Performance of the Malaysian Halal F&B Companies - Mohammad Aminuddin Sham; Faridah Hj Hassan; Abdul Kadir Othman (Asia Pacific Journal of Social Science Research, 2021)
Malaysia’s halal F&B companies are hampered by issues surrounding innovation and marketing such as low level of innovation, competitiveness and commercialisation. In understanding these problems, this study focused on the relationship between innovation and strategic marketing with regards to companies’ performance of the Malaysia halal food and beverage (F&B) companies which will be moderated by market turbulence. In this research, the sampling consists of 386 Malaysian companies from the halal F&B industry. In order to determine the interrelation of the variables, a Pearson’s bivariate correlation analysis was conducted followed by multiple regression analysis, which was used to test the level of influence of the independent variables and companies’ performance. From the findings, it can be concluded that Malaysian companies especially the SMEs emphasize on technological type innovation to ensure their performance in the market. The study also highlights on the emphasis given by Malaysia halal F&B companies on operational marketing and strategic marketing drivers in ensuring the growth of their business performance. Another important finding of the study is that even though Malaysia’s halal F&B companies emphasise on technological innovation, under the presence of market turbulence, the technological innovation has to be supported through non-technological innovations. Lastly, in the context of innovation, Malaysian halal F&B companies are looking at strategic marketing as important factors for business performance sustainability. Besides consolidating the existing theory on the importance of innovation and strategic marketing for explaining a variation in companies’ performance and the moderating role of market turbulence in the relationship, the findings of this study also reinforce the view of the industry on the critical role of innovation and strategic marketing in companies’ performance towards developing the halal F&B industry in Malaysia